Pengembangan Media Video Permainan Tradisional Suku Sasak untuk Pelestarian Budaya dan Sumber Belajar Muatan Lokal - Ikawati, Hastuti Diah; Purmadi, Ary; Anwar, Zul; Zulfakar, Zulfakar (JTP - Jurnal Teknologi Pendidikan, 2018)
This study was advance research from the result ofprevious study. Based on the study before was found at least 15 kinds of Sasak traditional games which often played. As we knew the games started disappeared. The traditional games have documented in printed form. Thus for, it can be used as a study supplement in Local Subject Matter. It aimed to facilitate the students to learn and play of the Sasak traditional games. Then, we developed the traditional games of Sasak. This study used ADDIE Model (Analysis, Design, Development, Implement and Evaluation). The result of product validation by the experts found the average score was 83,48%. While the result of the assessment by the students in individual and wide group testwere 91,52% and 82,32%. Based on the result, it can be concluded that the video development was suitable to use as a learning resource.